Al-Ittihadiyah's Gait In The Field of Education in North Sumatra (Study of The History of Islamic Education) - Khairuddin Khairuddin (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
Al-Ittihadiyah is one of the oldest Islamic mass organizations (Ormas) in Indonesia, especially North Sumatra. Since its establishment on January 27, 1935, Al-Ittihadiyah has established its role as an Islamic organization engaged in education, da'wah, and social activities. This study attempts to analyze the progress of Al-Ittihadiyah in the field of education in North Sumatra. The focus of this study discusses these objectives from the historical aspect of Islamic education. This type of research uses a qualitative approach with a literature study method. Sources of data and study materials are obtained from relevant and credible scientific literature, based on research (scientific articles). The results of this study indicate that Al-Ittihadiyah's role in education in North Sumatra (formerly part of East Sumatra) is very large. This is indicated by (1) the initial policy of the establishment of Al-Ittihadiyah which was based on unifying efforts between the ulama and scholars in North Sumatra; (2) Al-Ittihadiyah education council which focuses on the establishment of Islamic (educational) colleges under the auspices of Al-Ittihadiyah (starting from Kindergarten level to High School level/equivalent); and (3) Establishing higher education institutions.